1999
DOI: 10.1021/ja9909879
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Solid-Phase Synthesis of Polyamides as Linkers

Abstract: Solid-phase peptide synthesis (SPPS) yields well-defined polyamides of repeat unit NH-Z-CO but requires protected derivatives and deprotection steps. Polyamides of repeat unit NH-Y-NH-CO-X-CO (e.g., Nylon 66) are made by polymerizing diacids with diamines, but the absence of protecting groups leads to heterogeneity of chain length. We have produced a new class of polymers by automated solid-phase synthesis without protecting groups:  polyamide chains NH-Y-NH-CO-X-CO containing a precise number of monomer units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 9 publications
0
44
0
3
Order By: Relevance
“…Starting from (1), a monodisperse polyamide pseudo-PEG 2219 The synthesis of pseudo-PEG 2219 was carried out without success using the building blocks glycolic anhydride and PEG 220 . was attached stepwise using the methodology described by Rose and Vizzavona 35 The dendrimer was synthesized using the methodology described in the general procedures for the scaffold (2). After Mtt removal and subsequent incorporation of CF, the peptide dendrimer was cleaved and purified by semipreparative RP-HPLC with a reverse-phase Symmetry 1 C18 (30 Â 100 mm, 5 m) column using gradient E to afford the title compound with a purity of apporximately 90% using gradient B. Dendrimer 7: Free Amine-PEG Polydisperse.…”
Section: Peptide Dendrimersmentioning
confidence: 99%
“…Starting from (1), a monodisperse polyamide pseudo-PEG 2219 The synthesis of pseudo-PEG 2219 was carried out without success using the building blocks glycolic anhydride and PEG 220 . was attached stepwise using the methodology described by Rose and Vizzavona 35 The dendrimer was synthesized using the methodology described in the general procedures for the scaffold (2). After Mtt removal and subsequent incorporation of CF, the peptide dendrimer was cleaved and purified by semipreparative RP-HPLC with a reverse-phase Symmetry 1 C18 (30 Â 100 mm, 5 m) column using gradient E to afford the title compound with a purity of apporximately 90% using gradient B. Dendrimer 7: Free Amine-PEG Polydisperse.…”
Section: Peptide Dendrimersmentioning
confidence: 99%
“…The PPOs were synthesized on a solid support by successive coupling of succinic anhydride and (4,7,10)-trioxa-1,13-tridecanediamine (TTD) to produce oligomers of various, discrete lengths. 19 In a final step, N-bmaleimidopropionic acid was coupled to the PPO, providing suitable attachment chemistry to thiolgroups on the protein (Scheme 1B). High-pressure liquid chromatography (HPLC) and electrospray mass spectrometry (ES-MS) showed that the PPOs consisting of one to five subunits were O95% pure (data not shown) with yields between 30% and 40% based on the substitution of the starting resin (see Methods).…”
Section: Ppo Synthesismentioning
confidence: 99%
“…[14][15][16][17][18] The polyethyleneglycol-polyamide oligomers (PPO) consisted of multiple repeating units of succinic acid-(4,7,10)-trioxa-1,13 tridecanediamine. Discrete oligomers and polymers composed of this repeating unit have been used as inert peptide linkers 19 and as enhancers of the pharmacokinetic properties of protein pharmaceuticals, respectively. 20 Even short segments of the polymer greatly enhanced the solubility and handling of hydrophobic peptide segments, which is consistent with the presence of polyethylene oxide units in traditional detergents such as the Triton and Tween families.…”
Section: Introductionmentioning
confidence: 99%
“…For example, classic synthetic polymers such as polyamides -traditionally prepared by step-growth chemistry -can be prepared by solid-phase synthesis, for example, (i) by stepwise addition of succinic anhydride and a diamine, either a poly(ethylene glycol)-based diamine or 1,6-diaminohexane, without requiring any protection/deprotection steps [12] or (ii) by using succinic anhydride and a diamine, (S)-2-(9-fluorenylmethoxycarbonyl-amino)-1-propylamine, the diamine being protected to control the orientation of the chiral center [13]. The use of supported chemistry for the elaboration of well-defined polymers prepared by step-growth copolymerization is essential, since unsupported step-growth copolymerization of A-A and B-B comonomers, while allowing the preparation of alternating copolymers, do not lead to polymers with well-controlled molecular weight and architecture.…”
mentioning
confidence: 99%